Influence of geometry on stratification and segregation phenomena in bidimensional piles - Benito, Jesica Gisele (2014)
We present a numerical study of the flow segregation problem in bidimensional piles. To simulate the pile formation, we employ a pseudo-dynamics method. The model allows us to vary the concentration of big and small grains present in the pile and the size ratio between them. The different segregation patterns arising after the pile is finished are studied by analyzing the spatial distribution of the grains. Two different segregation indices are defined and evaluated over the piles. The contact network of the final configuration of grains in the pile is also determined. The conditions under which the different segregation patterns show up are discussed. A comparison with a previous experimental study is performed for all the numerical results obtained in the present paper. The advantages and limitations of the simulation model are also discussed.